Efeitos da administração aguda de zolpidem sobre as diferentes fases da memória em camundongos - Zanin, Karina Agustini [UNIFESP] (2010)
Zolpidem is an imidazopyridine agent with crescent therapeutic employment which binds selectively to the BZ1 site into the GABAA receptors. This selectivity seems to confer zolpidem its mainly hypnotic properties with relative absence of side effects which are associated to classical benzodiazepines, for example anticonvulsant and miorelexant effects and, importantly, amnesia. Although, clinical studies and in animal models have demonstrated amnestic effects after the acute administration of zolpidem. In this context, considering its crescent employment in the insomnia treatment, it is necessary to characterize the cognitive effects induced by this drug and also its effects on exploratory activity and emotionality. Thus, our results suggest that the pre-training acute administration of zolpidem promoted learning impairments on the dose of 10 mg/Kg, but not on the doses of 2 and 5 mg/Kg, and promoted a decrement on exploratory activity in a dose-dependent manner, but did not modified anxiety. In respect with memory, we observed retention deficits on the doses of 5 and 10 mg/Kg. When administered immediately after training, all animals had their memory preserved. Still, the pre-test administration of all doses of zolpidem did not modify animal’s performance, showing the lack of effects on retrieval. In parallel, our result did not suggest the influence of state-dependency phenomenon once the acute administration of zolpidem before training and testing did not reverse the memory impairment induced by pre-training administration of this drug. In relation to non-associative memory, we observed that 10 mg/Kg zolpidem promoted habituation deficits on the open-field model. Furthermore, it promoted a decrement on exploratory activity, corroborating previous results. In this way, we demonstrated that besides its selectivity, zolpidem can induce associative memory deficits (as non-associative) when administered before the training of the task interfering, maybe, on the consolidation process.